2009
DOI: 10.1097/bsd.0b013e31815ea8b6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of the Recurrent Laryngeal Nerve Irritation by Employing Spontaneous Intraoperative Electromyographic Monitoring During Anterior Cervical Discectomy and Fusion

Abstract: Our study indicates that laryngeal IEMG is a high-sensitivity modality that can provide real-time information and can potentially minimize the risk of operative RLN injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The sensitivity of monitoring was calculated at 100%, the specificity at 87%, the positive predictive value at 16%, and the negative predictive value at 97%. Thus, the authors concluded that “laryngeal intraoperative electromyography is a high-sensitivity modality that can provide real-time information and can potentially minimize the risk of operative RLN injury.” 15 …”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of monitoring was calculated at 100%, the specificity at 87%, the positive predictive value at 16%, and the negative predictive value at 97%. Thus, the authors concluded that “laryngeal intraoperative electromyography is a high-sensitivity modality that can provide real-time information and can potentially minimize the risk of operative RLN injury.” 15 …”
Section: Discussionmentioning
confidence: 99%
“…[41114] Thus, within the past two decades, increased emphasis has been placed on developing intraoperative neurophysiologic methods to accurately monitor the integrity of the spinal cord during spinal surgery. [589] Currently, one such widely used technique is SSEP.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recently published study found increased levels of recurrent laryngeal irritation (on intraoperative electromyography studies) with self-retained retractors compared with hand-held retractors with periodic soft-tissue release. 7 Dysphonia may also be caused by laryngeal damage due to its compression onto the unyielding shaft of the endotracheal tube, which is fixed distally by the balloon cuff and proximally by tape at the mouth. 13 This happens with the laryngeal displacement that occurs with retraction.…”
Section: Retraction-related Complicationsmentioning
confidence: 99%